Altered central pain processing after pancreatic surgery for chronic pancreatitis. Issue 13 (December 2013) - Bouwense, S. A.; Ahmed Ali, U.; ten Broek, R. P.; Issa, Y.; van Eijck, C. H.; Wilder‐Smith, O. H.; van Goor, H.
<x xml:space="preserve">Abstract</x> Background Chronic abdominal pain is common in chronic pancreatitis (CP) and may involve altered central pain processing. This study evaluated the relationship between pain processing and pain outcome after pancreatic duct decompression and/or pancreatic resection in patients with CP. Methods Patients with CP underwent quantitative sensory testing. Pain processing was measured via electrical pain detection (ePDT) and electrical pain tolerance (ePTT) thresholds in dermatomes C5 and L4. Inhibitory descending pain control mechanisms were assessed using the conditioned pain modulation (CPM) paradigm. Healthy controls and patients with CP were compared, and patients with CP and a poor pain outcome (visual analogue scale (VAS) score greater than 30) were compared with those with a good pain outcome (VAS score 30 or less). Results Forty‐eight patients with CP had lower ePDT, ePTT and CPM responses compared with values in 15 healthy controls (P < 0·030). The sum of ePDT values was lower in patients with a poor pain outcome than in those with a good outcome (median 7·1 versus 11·2 mA; P = 0·008). There was a correlation with the VAS score and the sum of ePDT values (rs = −0·45, P = 0·016) and ePTT values (rs = −0·46, P = 0·011), and CPM response (rs = −0·43, P = 0·006) in patients with CP. Conclusion After pain‐relieving pancreatic surgery, patients with CP exhibit altered central pain processing compared with that in healthy controls. Poor pain outcomes are associated with more central sensitization and more pronociceptive descending pain modulation, and this should be considered when managing persistent pain after pain‐relieving surgery for CP. Presented in part to the 7th Alpine Liver and Pancreatic Surgery Meeting, Madonna di Campiglio, Italy, January 2012, and the American Pancreatic Association/International Association of Pancreatology Joint Annual Meeting, Miami, Florida, USA, October–November 2012; published in abstract form as Pancreas 2012; 41: 1350